DNA-Sequence Based Typing of the Cronobacter Genus Using MLST, CRISPR-cas Array and Capsular Profiling - Ogrodzki, Pauline; Forsythe, Stephen J. (Frontiers in Microbiology, 2017)
The Cronobacter genus is composed of 7 species, within which a number of pathovars have been described. The most notable infections by Cronobacter spp. are of infants through the consumption of contaminated infant formula. The description of the genus has greatly improved in recent years through DNA sequencing techniques, and this has led to a robust means of identification. However some species are highly clonal and this limits the ability to discriminate between unrelated strains by some methods of genotyping. This article updates the application of three genotyping methods across the Cronobacter genus. The three genotyping methods were multilocus sequence typing (MLST), capsular profiling of the K-antigen and colanic acid (CA) biosynthesis regions, and CRISPR-cas array profiling. A total of 1654 MLST profiled and 286 whole genome sequenced strains, available by open access at the PubMLST Cronobacter database, were used this analysis. The predominance of C. sakazakii and C. malonaticus in clinical infections was confirmed. The majority of clinical strains being in the C. sakazakii clonal complexes (CC) 1 & 4, sequence types (ST) 8 & 12 and C. malonaticus ST7. The capsular profile K2:CA2, previously proposed as being strongly associated with C. sakazakii and C. malonaticus isolates from severe neonatal infections, was also found in C. turicensis, C. dublinensis and C. universalis. The majority of CRISPR-cas types across the genus was the I-E (Ecoli) type. Some strains of C. dublinensis and C. muytjensii encoded the I-F (Ypseudo) type, and others lacked the cas gene loci. The significance of the expanding profiling will be of benefit to researchers as well as governmental and industrial risk assessors.